Effects of nitrogen rate, time and method of application on blast and grain yield in upland rice - Santos, Alberto Baêta dos; Prabhu, Anne Sitarama; Aquino, Antonio Renes Lins de; Carvalho, José Ruy Porto de (Pesquisa Agropecuaria Brasileira, 2014)
The effects of timing application methods and levels of N on the incidence of blast disease (Pyricularia oryzae Cav.) in upland rice plants (Oryza sativa L.) cv. IAC 47 and on grain yield. The treatments were five levels (0, 15, 30, 45 and 60 kg/ha) of N applied in five planting times combined with the following application methods: 1. all the N in furrow; 2. all the N brodcasted at painting time; 3. 1/3 of N brodcasted at planting + 2/3 in top dressing, 4.1/3 of N in furrow + 2/3 in top dressing. 5. all the N at panicle initiation stage. Leaf and panicle blast increased with the increasing levels of N when applied in furrow at planting time. While tiller and panicle numbers increased, 100 - grain weight and filled grains/panicle decreased with increased N levels. Grain yield increased significantly up to 35 kg/ha of N when applied at the panicle initiation, under mild drought stress. But under prolonged drought stress, yield response was negative to N broadcasted at planting time or 1/3 at planting + 2/3 in top dressing.
Keywords: Pyricularia oryzae; Oryza sativa; nitrogen fertilizer